MENINGKATKAN PROFESIONALISME GURU MELALUI PEMBELAJARAN BAHASA INDONESIA BERBASIS MEDIA SOSIAL - Anggraini, Nani (LPPM STKIP PGRI Bandar Lampung, 2016)
Professionalism can be realized by improving the ability of teachers to master the advances of technology and information. One form of technological progress is the widespread use of social media as a means of communication and interaction in the community. The teacher can take advantages of social media in the application of learning in schools, especially in Indonesian Language subjects. Facebook, Twitter, and Blog media can be used by teachers in the process of learning the Indonesian language, especially in the ability to read and write. Utilization of social media will create a learning atmosphere that is exciting, innovative, and fun with a view to achieving the learning objectives optimally.